144 Charles Street, January 14, 1973 - Waid, C. Franklin (Tufts Archival Research Center, 2005)
Street-level view of the Charles Street Garage located at 144 Charles Street between Revere Street to the south and Dartmouth Street to the north. The facade of the building faces east-southeast towards Charles Street. A street lamp and parking meters line the sidewalk in front of the garage. Automobiles are parked along the curb. Commercial products are visible in the garage's street-level windows. 7 3/8 x 9 3/8, 7 7/8 x 9 7/8 overall Photographs